Gender, Livelihood, and Ecotourism during Covid-19 Epidemic in North Halmahera of Indonesia - Yerik Afrianto Singgalen; Astuti Kusumawicitra; Manuel Brito (UIN K.H. Abdurrahman Wahid Pekalongan, 2021)
This article aims to describe women's role in maintaining livelihoods in the tourism sector during the Covid-19 pandemic. The perspectives used are gender, livelihood, and ecotourism. This research location is in Tanjung Bongo Tourism Object and Kupa-Kupa Beach Tourism Object, North Halmahera Regency, Indonesia. The research method used is qualitative. The data collection techniques used were in-depth interviews, observation, and document study. This study's results indicate the role of women in maintaining livelihoods through business in the tourism sector. In the framework of sustainable livelihoods, limited access to capital affects the capability to support a tourism sector's business. On the other hand, women entrepreneurs in each tourism destination adhere to ecotourism principles to maintain a clean environment and safety and comfort in traveling. Based on this study's results, gender, livelihood, and ecotourism theoretically support sustainable eco-tourism.